How Top Glove Becomes the Largest Glove Producer - Daisy Mui Hung Kee; Jia Yee Lee; Yue Si Lee; Poh Lian Lim; Yi Min Loh; Yhixuan Hoe (Journal of the Community Development in Asia (JCDA), 2021)
Top Glove as the world’s largest glove producer provides quality and efficient gloves for healthcare purposes. This study is conducted to investigate key success factors that lead Top Glove to become a successful company. The study also gathered information about the challenges that Top Glove is facing to examine how Top Glove took over the obstacles and used its success factors to maintain its position in this industry. The findings indicate leadership, image and reputation, organizational innovation and employee satisfaction are the main contributing factors of Top Glove success.